The Effect of Childhood Obesity on Psychomotor Behavior - Khalfani, Muhammad Adrian; Rejeki, Purwo Sri; , Sakina; Fathil, Nur Ezza Fazleen Mohd (Folia Medica Indonesiana, 2023)
Childhood obesity is a complex problem, and its prevalence among school-age children has been found to have a greater impact on their physical well-being compared to their learning difficulties. In some cases, teachers or schools may not pay enough attention to issues that have the potential to affect or delay the psychomotor development of children. Therefore, this study aimed to provide enhanced comprehension regarding the effect of childhood obesity on psychomotor behavior. This study used a systematic review methodology to synthesize information regarding the effect of obesity on children's health and development. The information and data presented in this study were obtained from several scientific sources accessed through online libraries such as PubMed, ScienceDirect, and the Cochrane Library. A comprehensive search was conducted to identify scholarly publications, which resulted in a total of 815 papers published between 2013 and 2022. The selected papers exclusively consisted of original research articles that primarily focused on investigating the relationship between obesity in children aged 5–14 years and their psychomotor abilities and development outcomes. Following the screening process, five studies were found to meet the specified criteria. The findings of the selected studies revealed a substantial resemblance, specifically the correlation between childhood obesity and poor motor skills. Furthermore, the selected studies discovered that an increase in body fat is commonly associated with a rise in total body weight, or the relative body mass index (BMI), in both adults and children. Some studies demonstrated significant differences in the performance of diverse psychomotor variables according to children's BMI. According to the results of the studies, children with a higher BMI showed inferior performance in motor activities as a result of compromised body control and balance that inhibited the children's movement. This systematic review concludes that obesity has an effect on the psychomotor behavior of children.